2015
DOI: 10.1530/eje-15-0176
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil:lymphocyte ratio is positively related to type 2 diabetes in a large-scale adult population: a Tianjin Chronic Low-Grade Systemic Inflammation and Health cohort study

Abstract: Aim: It is widely known that inflammation is related to type 2 diabetes (T2D), but few studies have shown a direct relationship between the immune system and T2D using a reliable biomarker. Neutrophil:lymphocyte ratio (NLR) is an easy-to-analyze inflammation biomarker, but few studies have assessed the relationship between NLR and T2D. In order to evaluate how NLR is related to T2D, we designed a large-scale cross-sectional and prospective cohort study in an adult population. Subjects and methods: Participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 43 publications
2
49
2
2
Order By: Relevance
“…[19][20][21] This association persisted even when participants with chronic disease were excluded, and after adjustment for multiple confounding factors, supporting that shiftwork might independently contribute to systemic inflammation. Previous studies have also reported higher systemic inflammation in shiftworkers [31,32], and this might be one mechanism through which shiftwork could contribute to the risk of cardiometabolic disease.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…[19][20][21] This association persisted even when participants with chronic disease were excluded, and after adjustment for multiple confounding factors, supporting that shiftwork might independently contribute to systemic inflammation. Previous studies have also reported higher systemic inflammation in shiftworkers [31,32], and this might be one mechanism through which shiftwork could contribute to the risk of cardiometabolic disease.…”
Section: Discussionmentioning
confidence: 83%
“…The ratio of neutrophils to lymphocytes (NLR) [19] was calculated from analysis of a blood sample collected from each participant at the time of attending the UK Biobank assessment centre, and used as a marker of immune activation, that could be suggestive of higher inflammation. Immune activation is thought to contribute to the pathophysiology of diabetes, and the NLR have been previously been specifically associated with metabolic disease [20,21]. Self-reported diabetes and cardiovascular disease were recorded by questionnaire, as well as family history of diabetes, hypertension or depression (Supplementary methods).…”
Section: Exposures and Outcomesmentioning
confidence: 99%
“…1A and Supplemental Table 2). The neutrophil:lymphocyte ratio (NLR), a biomarker associated with TB severity 10 , insulin resistance and type 2 DM 11, 12 and coronary artery disease risk 13, 14 was higher in the TB and TBDM subgroups compared to DM and to healthy controls. Participants with TBDM had lower serum triglycerides and lower HDL than the DM subgroup (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the USA general population examination survey (NAHNES), the NLR average was 2.15, ranging from 2.06 to 2.44 according to ethnicity, sex, education, age, BMI, smoking, alcohol drinking, diabetes or heart conditions [16]. Also many chronic conditions are known to increase the body inflammatory status [17]. …”
Section: Introductionmentioning
confidence: 99%